2016
DOI: 10.3892/or.2016.5117
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-101 regulates T-cell acute lymphoblastic leukemia progression and chemotherapeutic sensitivity by targeting Notch1

Abstract: The present study aimed to investigate the role of microRNA (miR)-101 in acute lymphoblastic leukemia progression and chemoresistance. Furthermore, a novel target gene of miR-101 was identified. Here, we confirmed that miR-101 was significantly downregulated in the blood samples of patients with T-cell acute lymphoblastic leukemia (T-ALL) compared with the healthy controls, as determined by reverse transcription quantitative polymerase chain reaction (RTqPCR) analysis. The in vitro experiments demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
(29 reference statements)
0
29
0
Order By: Relevance
“…22,23 It has been shown the expression levels of miR-181a, miR-128-3P and miR-142-3p were significantly up-regulated in T-ALL patients, 1,4,24 whereas miR-204, miR-101 and miR-193b-3p were down-regulated. 2,24,25 Some studies have indicated that FBXW7 dysregulates important signaling pathways including Notch1 and Notes: a Targeting of FBXW7 is confirmed by the software. b Targeting of FBXW7 is not confirmed by the software.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…22,23 It has been shown the expression levels of miR-181a, miR-128-3P and miR-142-3p were significantly up-regulated in T-ALL patients, 1,4,24 whereas miR-204, miR-101 and miR-193b-3p were down-regulated. 2,24,25 Some studies have indicated that FBXW7 dysregulates important signaling pathways including Notch1 and Notes: a Targeting of FBXW7 is confirmed by the software. b Targeting of FBXW7 is not confirmed by the software.…”
Section: Discussionmentioning
confidence: 97%
“…Introduction T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematologic malignancy results from leukemic transformation of developing thymocytes, 1,2 representing nearly 25% of adult and 10-15% of childhood ALL cases. 2,3 Several cytogenetic abnormalities and genetic aberrations have been associated with the etiology of T-ALL. 1,4 Some functions including self-renewal, proliferation and survival, and blocked differentiation of precursor T cells are affected by these genetic aberrations.…”
mentioning
confidence: 99%
“…In addition to lymphoma, the relationship between miR-101 and the incidence of lymphoblastic leukemia has also been reported. Qian et al (32) showed that the expression of miR-101 in the peripheral blood of patients with lymphoblastic leukemia was decreased significantly compared with healthy individuals. In addition, they also found that the expression of miR-101 in the peripheral blood cells of patients with acute T lymphoblastic leukemia was significantly less than miR-101 expression in the healthy thymus and bone marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of the anti-apoptotic factor, Bcl-2, was significantly reduced, lymphoma cell proliferation was significantly decreased, and apoptosis was significantly increased. Qian et al (32) showed that in the process of the pathogenesis of lymphocytic leukemia, miR-101 acts as a tumor suppressor. Moreover, overexpression of miR-101 was found to decrease the proliferation and invasion of Jurkat lymphocytic leukemia cells, significantly increase apoptosis, and increase the sensitivity of the chemotherapy drug, doxorubicin, by targeting inhibition of the Notch1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear donor cell is a crucial factor affecting SCNT embryo quality and the efficiency of SCNT, and many efforts have been made to improve them by improving donor-cell status Mizutani et al, 2015). Furthermore, miR-101 can regulate cell proliferation, the cell cycle, and apoptosis in different cell types (Wang et al, 2014b;Zhou et al, 2015;Qian et al, 2016). Therefore, we detected the apoptosis, cell cycle, and proliferation in donor cells after miR-101-2 overexpression.…”
Section: Effects Of Mir-101-2 Overexpression On Apoptosis Cell Cyclementioning
confidence: 95%